Aplikasi Pemberian Pupuk Campuran Tithonia dan Pupuk Kandang Kotoran Sapi untuk Tanaman Bunga Mawar di Pot di Kelompok Ibu-Ibu PKK RT 20 Kelurahan Pakuan Baru Kota Jambi - Nasution, Hasriati; Suryanto, Suryanto; Saad, Asmadi; Yusfaneti, Yusfaneti (Studium: Jurnal Pengabdian Kepada Masyarakat, 2025)
Roses (Rosa sp.) are called the queen of all flowers because of their beauty, elegance, and fragrance. This ornamental plant possesses high economic value, attracts strong consumer demand, and can be cultivated commercially and systematically in alignment with market needs. In addition, many of the chemical contents in this flower make it a medicinal raw material, such as aroma therapy, anti-seizure, menstrual regulator, bile secretion medicine, and fever reducer. In order for rose plants to thrive and produce abundant flowers, they need sufficient nutrients, which can be provided through a mixture of Tithonia and cow dung manure. By mixing these two types of compost, the physical properties of the soil and the availability of microorganisms that decompose organic matter can be improved, allowing roses to grow more vigorously and produce more flowers. This community service activity aims to enhance the skills of PKK women in RT 20, Pakuan Baru Village, Jambi City in planting roses. The team conducted two stages, delivering material and direct practice. After the counseling, it was seen that the PKK women could receive the material explanation well.